2022
DOI: 10.3390/nu14030439
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity and Mechanism of Cryptochlorogenic Acid from Ageratina adenophora

Abstract: Ageratina adenophora is an invasive plant known for its toxicity to livestock. Current research on this plant has shifted from toxicity prevention to the beneficial utilization of plant resources. This study was performed to investigate the effects and mechanisms of cryptochlorogenic acid (CCGA) isolated from Ageratina adenophora on the inflammatory responses induced by lipopolysaccharide (LPS) in RAW264.7 cells. RAW264.7 cells were pretreated with CCGA (200, 100, and 50 μg/mL) and subsequently stimulated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Among these, oddioside A ( 1 ) and compounds 5 , 6 , 7 , 8 , 10 , 13 , 14 and 15 showed strong MMP-1 inhibitory activity. Several compounds isolated in the present study have already been reported for various effects such as anti-inflammatory ( 9 , 10 , 13 , 14 , 15 , 16 ), antioxidant ( 3 , 4 , 5 , 8 , 9 , 13 , 14 , 15 , 19 ), and anti-aging ( 3 , 9 , 13 ) in various cell lines [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. Thus, further experiments were focused on the new compound 1 to investigate its potential as a bioactive compound.…”
Section: Discussionmentioning
confidence: 65%
“…Among these, oddioside A ( 1 ) and compounds 5 , 6 , 7 , 8 , 10 , 13 , 14 and 15 showed strong MMP-1 inhibitory activity. Several compounds isolated in the present study have already been reported for various effects such as anti-inflammatory ( 9 , 10 , 13 , 14 , 15 , 16 ), antioxidant ( 3 , 4 , 5 , 8 , 9 , 13 , 14 , 15 , 19 ), and anti-aging ( 3 , 9 , 13 ) in various cell lines [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. Thus, further experiments were focused on the new compound 1 to investigate its potential as a bioactive compound.…”
Section: Discussionmentioning
confidence: 65%
“…Isomers have been studied for beneficial effects: cryptochlorogenic acid for anti-inflammatory activity and antioxidative effects [ 23 , 24 ], and neochlorogenic acid for anti-inflammatory activity [ 25 ]. The bioactivities of cryptochlorogenic acid and neochlorogenic acid should be considered when explaining the beneficial effects of apples in the digestive system due to their relatively high amount (in the mouth up to 22% of the total chlorogenic acid amount before digestion of the peel; in the small intestine 41% and 12% of the total chlorogenic acid amount before digestion of the peel or flesh, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…However, more studies are necessary to understand this process, and to understand the fate of isomers of chlorogenic acids and their potential degradation in the environments of the different phases of digestion. Some studies showed the potential of the isomer cryptochlorogenic acid to attenuate inflammatory symptoms [ 23 , 24 ] and to inhibit oxidative stress [ 23 ]. Anti-inflammatory effects were shown for the isomer neochlorogenic acid as well [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, our putative identi cation has successfully discriminated isomers, e.g., luteolin 7-O-β-glucuronide (16) and scutellarin (23). Both of them showed a strong base peak m/z 285 and a weak molecular ion peak m/z 461, resulting in highly similar MS/MS pro les.…”
Section: Putative Identi Cation Based On Databasementioning
confidence: 91%